Effects of drospirenone and ethinylestradiol tablets (II) combined with metformin on the composition of gut microbiota in polycystic ovary syndrome with insulin resistance - Liu, Yanglu; Wang, Qingmei; Han, Lingling; Shao, Xue; Wang, Xin; Liu, Xin; Wang, Jiayi; Luo, Shuang; Lu, Baiyu (Frontiers in Endocrinology, 2025)
ObjectivesTo explore the relationship between polycystic ovary syndrome with insulin resistance (PCOS-IR) and gut microbiota by analyzing the composition characteristics of gut microbiota in PCOS without or with Insulin resistance (IR) and the changes before and after treatment.MethodsWomen with PCOS were recruited and divided into polycystic ovary syndrome without insulin resistance (PCOS-NIR) group and PCOS-IR group. The PCOS-NIR group was given oral drospirenone and ethinylestradiol tablets (II), and the PCOS-IR group was given oral drospirenone and ethinylestradiol tablets (II) combined with metformin hydrochloride tablets. The course of treatment was 3 months. Baseline data, blood and stool samples were collected before and after treatment. All those stool samples were used for 16S rDNA sequencing to analyze the composition of gut microbiota in each group and their correlation with biochemical parameters.Results1. Baseline data and biochemical parameters: before treatment, body mass index (BMI) in PCOS-NIR group was less than that in PCOS-IR group(P < 0.05). After treatment, CHO levels decreased in PCOS-NIR group (P < 0.05); FINS, LDL-C and HOMA-IR decreased and HDL-C levels increased in PCOS-IR group (P < 0.05). 2. Characteristics of gut microbiota: before treatment, there was no significant difference in α and β diversity between PCOS-NIR group and PCOS-IR group. The gut microbiota both of the two groups were mainly composed of Firmicutes, Fusobacteriia, Acidimicrobiia, Oscillospirales, Lachnospiracea, Ruminococcaceae. The relative abundance of Acidimicrobiia in PCOS-IR group was higher than that in PCOS-NIR group (P < 0.05). The relative abundance of Fusobacteriu in the PCOS-IR group was lower than that before treatment (P < 0.05). 3. Correlation between gut microbiota and biochemical parameters: before treatment, Acidimicrobiia was positively correlated with TG level in the PCOS-NIR group (P < 0.05); Acidimicrobiia was positively correlated with HOMA-IR in the PCOS-IR group (P < 0.05). After treatment, Fusobacterium in PCOS-IR group was negatively correlated with HDL-C level (P < 0.05).Conclusion1. There is a difference in the relative abundance of Acidimicrobiia in the gut between PCOS-NIR and PCOS-IR patients before treatment, which is positively correlated with HOMA-IR, suggesting that Acidimicrobiia may be involved in the occurrence of PCOS-IR. 2. Drospirenone and ethinylestradiol tablets (II) combined with metformin tablets can change the gut microbiota relative abundance of patients with PCOS-IR, which may be related to the improvement of host lipid and glucose metabolism.